Developing Effective Counseling Strategies for Visually Impaired Students: Personal, Social, Career, and Academic Perspectives - Ginting, Rafael Lisinus; Ellis, Rusnawaty; Violina, Erwita Ika; Asiah, Asiah (Guidance and Counseling Study Program, Pattimura University, 2024)
This study examines the guidance and counseling needs of visually impaired students, emphasizing the importance of tailored programs to address their unique challenges. Using a qualitative approach complemented by quantitative data collection, the research surveyed visually impaired students at SLB – A Karya Murni Medan. The findings reveal that personal needs, such as independent daily living activities, are the highest priority, followed by career needs, including career guidance and decision-making skills. Social needs, involving communication and social interaction, and academic needs, covering fundamental educational skills, were also significant. The analysis underscores the necessity of a comprehensive counseling program designed to support visually impaired students in achieving personal independence, career readiness, social skills development, and academic success. This program should incorporate a thorough understanding of students' needs, clear objectives, and robust implementation strategies to ensure their overall well-being and development.